2021
DOI: 10.3390/ma14143938
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Based Water Treatment Residuals: Phase, Physicochemical Characterization, and Textural Properties

Abstract: Groundwater treatment residuals (GWTRs) are safe waste materials generated during drinking water treatment. GWTRs are mainly deposited in landfills, but the preferred solution should be reused or utilized for some components. To ensure proper sludge management, it is important to provide quality, chemical composition, and texture characteristics of GWTRs. Therefore, in this study, we aimed to investigate and compare the features of GWTRs collected from four water treatment plants. GWTRs were characterized by X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Figure 8 shows FTIR spectra used to evaluate functional group differences between Fe-WTR and Al-WTR before and after adsorption. The blank group (before adsorption) shows -OH stretching vibration peaks (3440 cm −1 ) [87,88], -OH bending vibration peaks (1640 cm −1 ) [54], and Al/Fe-O stretching vibration peaks (470 and 536 cm −1 ) on the WTR surface [89][90][91]. In addition, the peaks at 1040 and 1080 cm −1 correspond to Al-OH bending vibrations [92,93].…”
Section: Possible Mechanisms Of Tl(i) Adsorptionmentioning
confidence: 99%
“…Figure 8 shows FTIR spectra used to evaluate functional group differences between Fe-WTR and Al-WTR before and after adsorption. The blank group (before adsorption) shows -OH stretching vibration peaks (3440 cm −1 ) [87,88], -OH bending vibration peaks (1640 cm −1 ) [54], and Al/Fe-O stretching vibration peaks (470 and 536 cm −1 ) on the WTR surface [89][90][91]. In addition, the peaks at 1040 and 1080 cm −1 correspond to Al-OH bending vibrations [92,93].…”
Section: Possible Mechanisms Of Tl(i) Adsorptionmentioning
confidence: 99%
“…This high Fe content is due to the Fe based coagulants used in the water treatment process [ 36 ]. Likus et al [ 97 ] also reported high Fe content (32–56%) in groundwater treatment residuals.…”
Section: Characteristics Of Water Treatment Residualsmentioning
confidence: 99%
“…Although these coagulants are effective in reducing the particle and organic hindrances; however, they may be non-cost effective and harmful; in addition, they need special store and handling requirements (Yamaguchi et al, 2021). The previous study conducted by Likus et al, (2021) reported that the coagulants may also cause secondary water problems, such as residual iron and aluminum species, as well as harmful synthetic polymers in the treated water. All the chemicals used in water purification are costly, thus the use of native products such as plant extracts for clarification and purification of drinking water in the underdeveloped nations is an urgent need (Delelegn et al, 2018;Yamaguchi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%